2007
DOI: 10.1159/000109822
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sodium-Glucose Cotransporter Activity and Aquaporin-2 Expression in Rat Kidney during Chronic Nitric Oxide Synthase Inhibition

Abstract: Background/Aims: The renal sodium glucose cotransporter (SGLT2) and the water channel aquaporin-2 (AQP2) play a critical role in tubular sodium and water reabsorption and in the regulation of extracellular fluid volume both in physiologic and pathophysiologic conditions. However, there is little information about SGLT2 and AQP2 expression and/or activity in hypertension and there are no reports during hypertension induced by chronic nitric oxide synthase (NOS) inhibition. Methods: Hypertension was induced in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
(59 reference statements)
2
10
0
Order By: Relevance
“…This is in accordance with a previous work of our laboratory, where we showed that AQP2 is down regulated in the renal medulla of rats made hypertensive by chronic inhibition of NOS [27]. Besides, we have recently demonstrated a synergistic effect of NO and NFATc (nuclear factor of activated T cells) promoting an increase in AQP2 mRNA and protein in mouse papilla and activation of the AQP2 promoter in kidney-derived cells [47].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with a previous work of our laboratory, where we showed that AQP2 is down regulated in the renal medulla of rats made hypertensive by chronic inhibition of NOS [27]. Besides, we have recently demonstrated a synergistic effect of NO and NFATc (nuclear factor of activated T cells) promoting an increase in AQP2 mRNA and protein in mouse papilla and activation of the AQP2 promoter in kidney-derived cells [47].…”
Section: Discussionsupporting
confidence: 93%
“…Animals were allowed to acclimatize to metabolic cages for two days and then fasted for 24 h before the collection of urine to avoid differences in plasma glucose concentration and NOx excretion due to different food intake. Urine samples (24 h) were analyzed for total protein by a turbidimetric method using trichloroacetic acid as previously described [27]. Urine analysis for glucose and ketones was carried out using reactive strips (Keto-Diastix Bayer Diagnostics S.A., Argentina).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were left to acclimatize to the metabolic cages for 2 days before the urine collection. Urine samples (24 h) were analyzed for urinary protein excretion (U p ) by a turbidimetric method using trichloroacetic acid [18] as previously described [19]. Urine analysis for urinary ketone excretion (U ketones ) was undertaken using a nitroprusside test (Keto-Diastix Bayer Diagnostics S.A., Buenos Aires, Argentina).…”
Section: Methodsmentioning
confidence: 99%
“…BBV from rat renal cortex were prepared by MgCl 2 precipitation and differential centrifugation as previously described [19]. The enrichment in BBV was determined previously by the increase in brush border markers such as γ-glutamyl transferase activity and sphingomyelin (SM) [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation